If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 6(x + -7) Reorder the terms: 24 = 6(-7 + x) 24 = (-7 * 6 + x * 6) 24 = (-42 + 6x) Solving 24 = -42 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 24 + -6x = -42 + 6x + -6x Combine like terms: 6x + -6x = 0 24 + -6x = -42 + 0 24 + -6x = -42 Add '-24' to each side of the equation. 24 + -24 + -6x = -42 + -24 Combine like terms: 24 + -24 = 0 0 + -6x = -42 + -24 -6x = -42 + -24 Combine like terms: -42 + -24 = -66 -6x = -66 Divide each side by '-6'. x = 11 Simplifying x = 11
| logx^2=5 | | 2x^2+34x+17=0 | | 12n+9=6 | | (x+3)(x+4)+(x+6)(x-3)= | | 19=-(5x+7) | | 4(y-7)=5-(6y-2) | | C=39.45+0.25x | | 8z=3 | | 7(4x+2)=42 | | X^2-4x=5x | | 2.5k+5-1.5.5k=14 | | x^2+2x-363=0 | | 4x-8=7+3 | | v=Ixt | | z^3-z^2-6=0 | | 3y=0.006 | | 6=10c | | 1-5x=x-13 | | Log(x+4)=8 | | (2x)=1 | | Y-(-12)=7 | | 12x-6=-11x | | x^2-18x=1.25 | | 4(5x-8)-3(2x-7)= | | 9(9x)=96x | | 8x=(3x^2)-2 | | 7x-3=4x-24 | | (6f-k)= | | 36m^6+12m^4=m^2+0 | | 8r^2+10r-12=0 | | 10x+3=100 | | 5[3(x+4)-2(1-x)]-x-35=14x+65 |